Numerical modeling of pollutant transport in the atmospheric boundary layer using ANSYS (International Journal of Mathematics and Physics, 2016)
The purpose of research is to simulate the dynamics of wind velocity distribution, impurities in the atmospheric boundary layer using ANSYS software system. Computational modeling is a basis for successful environmental problems researches, in particularly, to predict the spread of polluting substances, hazardous gas clouds and impurities in the air from man-made sources and optimization the financial costs of environmental measures. The solution of such problems requires the achievement of the following objectives: the mathematical model creation of the atmospheric boundary layer dynamics,design scheme description, setting the boundary and initial conditions, the process of problem solving, convergence solution control,the results processing and analyzing, what was done in this paper.   GMT АнглийскийИспанскийИтальянскийКазахскийКитайский ТрадКитайский УпрКорейскийРусскийТурецкийФранцузский АнглийскийИспанскийИтальянскийКазахскийКитайский ТрадКитайский УпрКорейскийРусскийТурецкийФранцузский        Звуковая функция ограничена 200 символами  Настройки : История : Обратная связь : DonateЗакрыть